Efficient Management of Road Construction Machinery in Local Governments - Rodríguez, Marcos (2025)
Management of construction equipment owned by local governments, used for the purpose of road construction and maintenance, is a critical success factor in road management for some municipalities. There is a technological dependency in using construction equipment to perform road management and construction of highway projects in some municipalities, however, the lack of management skills for planning and controlling the equipment can lead to constraints or obstacles in executing road projects or the misuse of money that was supposed to be used for road maintenance, then the opportunity to build better projects is partially or totally missed. This article explains the primary factors that should be planned and executed in order to develop a better equipment management in municipal governments for the benefit of the public and roads users. The factors are; the feasibility study before deciding to purchase a piece of equipment, the preventive maintenance program to preserve each machine, the daily work control system and the training actions for operators, the planning and budgeting to let the equipment work most part of the year and the detailed estimation of hourly cost for each equipment.